2022
DOI: 10.52979/raoa.1173
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de consultas por fracturas maxilofaciales en un servicio de urgencias odontológicas del Área Metropolitana de Buenos Aires

Abstract: Objetivo: Describir la incidencia, la causa, el patrón y el tratamiento de fracturas maxilofaciales en sujetos que solicitaron atención en un Servicio de Urgencias Odontológicas del Área Metropolitana de Buenos Aires. Materiales y métodos: Se analizaron las historias clínicas de los individuos que concurrieron al Servicio de Urgencias y Orientación de Pacientes de la Facultad de Odontología de la Universidad de Buenos Aires (SUyOP) en el período comprendido entre marzo de 2018 y diciembre de 2019. Se registró… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…whose objective was the position of retained lower third molars in patients seen in a Radiology Clinic in the city of Curitiba, Paraná, Brazil, applying the traditional classification of Pell & Gregory in patients aged 20 to 40 years, where the most frequent position was A, class II (43.43%), followed by position B, class II (39.73%). Similarly, in the study carried out by Gatti et al [1] in Buenos Aires, 949 panoramic radiographs were evaluated and the results showed that the most frequent position of mandibular third molar was IIA (28%).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…whose objective was the position of retained lower third molars in patients seen in a Radiology Clinic in the city of Curitiba, Paraná, Brazil, applying the traditional classification of Pell & Gregory in patients aged 20 to 40 years, where the most frequent position was A, class II (43.43%), followed by position B, class II (39.73%). Similarly, in the study carried out by Gatti et al [1] in Buenos Aires, 949 panoramic radiographs were evaluated and the results showed that the most frequent position of mandibular third molar was IIA (28%).…”
Section: Discussionmentioning
confidence: 86%
“…The third molar is the most frequently retained tooth, with a large variation between populations and ethnic groups (16.7-68.6%). Of all retained teeth, 98% are third molars [1]. A third molar is considered retained when it has not fully erupted to its normal position in the occlusal plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation